Unlikely Heroes : The Place of Holocaust Rescuers in Research and Teaching - Steinacher, Gerald; Kohen, Ari, 1977- (Book collections on Project MUSE., 2019)
Classes and books on the Holocaust often center on the experiences of victims, perpetrators, and bystanders, but rescuers also occupy a prominent space in Holocaust courses and literature even though incidents of rescue were relatively few and rescuers constituted less than 1 percent of the population in Nazi-occupied Europe. As inspiring figures and role models, rescuers challenge us to consider how we would act if we found ourselves in similarly perilous situations of grave moral import. Their stories speak to us and move us. Yet this was not always the case. Seventy years ago these brave men and women, today regarded as the Righteous Among the Nations, went largely unrecognized; indeed, sometimes they were even singled out for abuse from their co-nationals for their selfless actions. Unlikely Heroes traces the evolution of the humanitarian hero, looking at the ways in which historians, politicians, and filmmakers have treated individual rescuers like Raoul Wallenberg and Oskar Schindler, as well as the rescue efforts of humanitarian organizations. Contributors in this edited collection also explore classroom possibilities for dealing with the role of rescuers, at both the university and the secondary level.